2017
DOI: 10.20944/preprints201705.0068.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Treated Greywater Reuse for Hydroponic Lettuce Production in a Green Wall System – Quantitative Health Risk Assessment

Abstract: Abstract:The scarcity and pollution of freshwater are extremely crucial issues today and the expansion of water reuse have been considered as an option to reduce its impact. This study aims to assess the efficiency of an integrated greywater treatment system and hydroponic lettuce production as a part of a green wall structure and to evaluate the health risk associated with the production and consumption of lettuce through quantitative microbial risk assessment (QMRA) and chemical health risk assessment. The s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, Cu can be toxic to a number of plants at concentrations of 0.1-1.0 mg/L, and Zn can be toxic to many plants at widely varying concentrations, especially at 10 mg/L in reclaimed water, which requires short-term use (U.S. EPA 2012). This is similar to other research, which found that Zn and Cu were detected in the lettuce tissue at relatively high levels compared with the other elements (Eregno et al 2017). Pb accumulated at high levels in coriander in all plots.…”
Section: Exposure Assessmentsupporting
confidence: 91%
“…However, Cu can be toxic to a number of plants at concentrations of 0.1-1.0 mg/L, and Zn can be toxic to many plants at widely varying concentrations, especially at 10 mg/L in reclaimed water, which requires short-term use (U.S. EPA 2012). This is similar to other research, which found that Zn and Cu were detected in the lettuce tissue at relatively high levels compared with the other elements (Eregno et al 2017). Pb accumulated at high levels in coriander in all plots.…”
Section: Exposure Assessmentsupporting
confidence: 91%
“…Antimicrobial resistant strains of such pathogens were also of concern ( Aarestrup et al, 2008 ), especially in environments where continuous exposure to antimicrobials could induce resistance in microbiota ( Checcucci et al, 2020 ; García et al, 2020 ; Xi et al, 2015 ). Among protozoa, the addressed pathogens were mainly Cryptosporidium ( Eregno et al, 2017 ) and Giardia ( Srikanth & Naik, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, more or less stabilized organic substances, if poorly preserved and stored, can serve as excellent substrates for pathogens and become carriers of infections [21].…”
Section: Pathogensmentioning
confidence: 99%